Admission Levels of Total Tau and β-Amyloid Isoforms 1–40 and 1–42 in Predicting the Outcome of Mild Traumatic Brain Injury - Hossain, Iftakher; Mohammadian, Mehrbod; Takala, Riikka S. K.; Tenovuo, Olli; Azurmendi Gil, Leire; Frantzén, Janek; van Gils, Mark; Hutchinson, Peter J.; Katila, Ari J.; Maanpää, Henna-Riikka; Menon, David K.; Newcombe, Virginia F.; et al. (Frontiers in Neurology, 2020)
Background: The purpose of this study was to investigate if admission levels of total tau (T-tau) and β-amyloid isoforms 1-40 (Aβ40) and 1-42 (Aβ42) could predict clinical outcome in patients with mild traumatic brain injury (mTBI). Methods: A total of 105 patients with mTBI [Glasgow Coma Scale (GCS)≥13] recruited in Turku University Hospital, Turku, Finland were included in this study. Blood samples were drawn within 24 hours of admission for analysis of plasma T-tau, Aβ40 and Aβ42. Patients were divided into computed tomography (CT)-positive and CT-negative groups. The outcome was assessed 6-12 months after the injury using the Extended Glasgow Outcome Scale (GOSE). Outcomes were defined as complete (GOSE=8) or incomplete (GOSE<8) recovery. The Rivermead Post Concussion Symptoms Questionnaire (RPCSQ) was also used to assess mTBI-related symptoms. Predictive values of the biomarkers were analyzed independently, in panels and together with clinical parameters. Results: The admission levels of plasma T-tau, Aβ40 and Aβ42 were not significantly different between patients with complete and incomplete recovery. The levels of T-tau, Aβ40 and Aβ42 could poorly predict complete recovery, with areas under the receiver operating characteristic curve 0.56, 0.52 and 0.54, respectively. For the whole cohort, there was a significant negative correlation between the levels of T-tau and ordinal GOSE score (Spearman ρ=-0.231, p=0.018). In a multivariate logistic regression model including age, GCS, duration of posttraumatic amnesia, Injury severity score (ISS), time from injury to sampling, and CT findings, none of the biomarkers could predict complete recovery independently or together with the other two biomarkers. Plasma levels of T-tau, Aβ40 and Aβ42 did not significantly differ between the outcome groups either within the CT-positive or CT-negative subgroups. Levels of Aβ40 and Aβ42 did not significantly correlate with outcome, but in the CT-positive subgroup, the levels of T-tau significantly correlated with ordinal GOSE score (Spearman ρ=-0.288, p=0.035). The levels of T-tau, Aβ40 and Aβ42 were not correlated with the RPCSQ scores. Conclusion: The early levels of T-tau are correlated with the outcome in patients with mTBI, but none of the biomarkers either alone or in any combinations could predict complete recovery in patients with mTBI.